Comparative study of nanohydroxyapatite microspheres for medical applications (2008)
This study concerns the preparation, physical, and in vitro characterization of two different types of hydroxyapatite (HA) microspheres, which are intended to be used as drug-delivery systems and bone-regeneration matrices. Hydroxyapatite nanoparticles (HA-1 and HA-2) were prepared using the chemical precipitation synthesis with H3PO4, Ca(OH)2, and a surfactant, SDS (sodium dodecyl sulfate), as starting reagents. The HA powders were dispersed in a sodium alginate solution, and spherical particles were obtained by droplet extrusion coupled with ionotropic gelation in the presence of Ca2þ. These were subsequently sintered to produce HA-1 and HA-2 microspheres with a uniform size and interconnected microporosity. Both powders and microspheres were characterized using FTIR and X-ray diffraction. Moreover, SEM and mercury intrusion porosimetry were used to analyze the microspheres, and TEM was used to analyze the powders. Results showed that pure HA and mixtures of HA/b-TCP in the nanometer range and needlelike shape were obtained for HA-1 and HA-2 powders, respectively. Neutral Red, scanning electron microscopy and confocal microscopy were used to evaluate the behavior of osteoblastic-like MG-63 cells cultured on HA microspheres surfaces for 7 days. Results showed that good adhesion and proliferation of osteoblasts on the HA microspheres surface. Cells built bridges between adjacent microspheres, forming microspheres-cells clusters in both types of materials. 2007 Wiley Periodicals, Inc. J Biomed Mater Res 86A: 483–493, 2008.